Age-of-Acquisition Effects in Novel Picture Naming: A Laboratory Analogue. Issue 9 (September 2013) - Catling, Jonathan; Dent, Kevin; Preece, Emma; Johnston, Robert
Age-of-acquisition (AoA) effects are such that early-acquired items are more quickly recognized and produced than later acquired items. In this laboratory analogue, participants were trained to name a group of Greeble pictures with a novel nonsense name. We manipulated order of acquisition of the stimuli: Half of the stimuli were presented from the onset of training (early acquired) whilst the other half were introduced later in the training schedule (late acquired). At test, when early and late stimuli had equal cumulative frequency, early stimuli were named significantly faster than late items. In a second test, it was also found that visual duration thresholds were significantly smaller for the early items when participants were asked to name the critical items. These findings support the notion that order-of-acquisition effects can be manifest over a short time span in the laboratory, and that the effect of order of acquisition is distinct from mere frequency of exposure. The findings are consistent with the idea that AoA effects occurring over a large temporal scale may be a special case of more general order-of-acquisition effects, and both may be a general property of learning mechanisms.